Co-creating learning and teaching : towards relational pedagogy in higher education - Bovill, Catherine (Critical practice in higher education., 2020)
Offers a unique perspective in bringing together the concept of co-creation with relational pedagogy within higher education learning and teaching. Highlights the benefits of classroom-level, relational, dialogic pedagogy and co-creation, with examples of practice and practical guidance.